Projeto Social em Regularização Fundiária Urbana: participação social e medidas sociais em REURB, Município de Sapucaia/PA - SILVA, Ielma Francione Assunção da (2022)
This work proposes the systematization of social measures within the scope of Land Regularization projects (REURB), configured in the format of a Social Project, aimed at populations residing in areas subject to urban land regularization, aiming to instrumentalize them to play the role of active agents. in the process, accessing the rights inherent to urban life and contributing to the sustainability of measures resulting from land tenure regularization with the population staying in the regularized area. It broke. of the reality of the city of Sapucaia/PA, especially the Sol Nascente neighborhood, and in a brief study, through documentary research and official statistical data, contacts with residents, leaders and direct observation, the main social demands were identified and the network mapped of local and surrounding institutional support, noting the lack of this resource in the municipality. In this perspective, general guidelines for the elaboration of the Social Project in REURB are presented in a broad way, in the perspective of subsidizing other municipalities from their social and institutional peculiarities, and specifically social measures for the municipality of Sapucaia, through actions collective, socio-organizational and training, consolidated in thematic axes, to be built and managed in a shared way between public power and society, giving the urban land regularization policy the status of public policy that brings to light the intrinsic needs of the urban population and points out ways for the conquest and expansion of rights, especially the right to the city.